Regularity of growth of fourier coefficients of entire functions of improved regular growth - Khats’, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We establish a criterion for the improved regular growth of entire functions of positive order with zeros on a finite system of half-lines in terms of their Fourier coefficients.